Cooperative Noncovalent Interactions Induce Ion Pair Separation in Diphenylsilanides. Issue 62 (17th October 2017) - Marro, Eric A.; Press, Eric M.; Purkait, Tapas K.; Jimenez, Daniel; Siegler, Maxime A.; Klausen, Rebekka S.
Abstract: This crystallographic and computational study describes an unusual potassium silanide structure. A contact ion pair is expected in the solid state between potassium and silicon, yet the potassium cation binds an aromatic ring and the anionic silanide interacts with CH bonds on neighboring crown ether molecules. These structure‐bonding phenomena are attributed to strong soft–soft interactions. Abstract : Both bound to the crown : This crystallographic and computational study describes an unusual separated ion pair in which crown ether molecules bind both cation and anion. These structure–bonding phenomena are attributed to strong soft–soft interactions.